Educational expenditure of large states: a normative view - Roy, Allen; Rao, M. Govinda; Kamaiah, B. (2000)
Utilising the pooled data for 15 large Indian states over the period 1992-93 to 1997-98, this study employs panel data models to estimate the normative (average) levels of expenditure on primary, secondary and higher education. The findings of the study reveal that the actual spending on educational services in low income states is lower than their `needs'. This finding implies that the existing fiscal equalisation mechanism has not been effective in offsetting the revenue and cost disabilities of the poorer states in India. - Reproduced
Keywords: Educational costs; Education